Proyecto de factibilidad para la creación de una empresa comercializadora a domicilio de artículos para el hogar (electrodomésticos, audio y video, línea de ollas y textiles) en la ciudad de Loja - Jaramillo Godoy, Nely Vicenta (2016)
This research work focuses on the analysis and necessary information to define the feasibility of a study of investment, which has as main objective to determine the advisability of establishing a trading company to address household items (appliances, audio and video, line of pots and textiles) in the city of Loja. During its development: first, it started with the concrete objectives for which it was raised and presents the market research, the technical and organizational study, the economic study and subsequently to evaluate this proposal financially. To run better this research was necessary to follow a chronological order of steps. They were developed as follows: The study starts with the introduction, which sets out clearly a slight preamble of research addressed, followed by literature review which was very necessary to reinforce the implicit and referential concepts in this project, as well as the materials and methods which were used in the development of the project. Then, the basic results of the research is presented in which all necessary information was obtained, determining the behavior of the target market in relation to customers and competitors in the marketing of housewares. In the discussion stage, it begins with the market research to determine the degree of acceptance that will have the new company. It continues with the technical and organizational study using administrative systems and processes, demonstrating the operational structure of the organization. The finance budgets and investments required for the establishment and operation of the business are evaluated, and it culminates with a financial study in which the sustainability of the project is defined. To conclude this research process, we have the respective conclusions and recommendations reached. It is the result of a hard research work, which certainly establishes a source of information for future studies.